Aktualisasi Disiplin Rohani Pada Kepemimpinan Gereja Lewat Model Kepemimpinan J. Oswald Sender - Juli Santoso; Susanti Embong Bulan (RERUM: Journal of Biblical Practice, 2023)
According To J. Oswald Senders that effective church leadership involves a blend of inner life growth and the use of leadership abilities from the outside. This approach emphasizes the importance of spiritual discipline in the character development of church leaders, which helps them lead the congregation effectively. Prayer, scripture study, communion, and Sabbath giving are identified as the four main areas of spiritual discipline in the Senders leadership paradigm. Church leaders can improve their relationship with God, gain insight into the needs of their community, and build a culture of spiritual growth within their church by prioritizing these behaviors. The purpose of this study that we need a leadership that is able to transform the character of the church, provide strategic changes, as well as those that can increase the potential of the individuals it leads, effectively manage resources and have the desire to be actively involved in the process of fighting discrimination still occurs in many parts. J. Oswald provided the basis for good spiritual leadership in church leadership.  The research method used is to examine the leadership model J. Oswald Senders and his application in church leadership in today's context. The result is the leadership model of J. Oswald Sanders applied to spiritual discipline in church leadership, namely establishing personal discipline, demonstrating discipline in how to manage others, and reviewing progress in achieving their goals regularly and adjusting strategies accordingly.   Menurut J. Oswald Senders bahwa kepemimpinan gereja yang efektif melibatkan perpaduan antara pertumbuhan kehidupan batin dan penggunaan kemampuan kepemimpinan dari luar. Pendekatan ini menekankan pentingnya disiplin rohani dalam pengembangan karakter pemimpin gereja, yang membantu mereka memimpin jemaat secara efektif. Doa, penelaahan kitab suci, persekutuan, dan sabat memberikan diidentifikasi sebagai empat bidang utama disiplin rohani dalam paradigma kepemimpinan Senders. Pemimpin gereja dapat meningkatkan hubungan mereka dengan Tuhan, mendapatkan wawasan tentang kebutuhan komunitas mereka, dan membangun budaya pertumbuhan rohani di dalam gereja mereka dengan memprioritaskan perilaku ini. Tujuan penelitian ini bahwa kita membutuhkan kepemimpinan yang mampu mentransformasikan karakter gereja, memberikan perubahan-perubahan strategis, sekaligus yang dapat meningkatkan potensi individu-individu yang dipimpinnya, efektif mengelola sumber daya dan memiliki keinginan untuk aktif terlibat dalam proses melawan diskriminasi masih terjadi dalam banyak bagian. J. Oswald memberikan dasar kepemimpinan rohani yang baik dalam kepemimpinan gereja.  Metode penelitian yang dipakai adalah meneliti kepemimpinan model J. Oswald Senders dan penerapannya di kepemimpinan gereja dalam konteks sekarang ini. Hasilnya adalah model kepemimpinan J. Oswald Sanders menerapkan pada disiplin rohani dalam kepemimpinan gereja, yaitu membangun disiplin pribadi, menunjukkan disiplin dalam cara mengatur orang lain, dan meninjau kemajuan dalam mencapai tujuan mereka secara teratur dan menyesuaikan strategi sebagaimana mestinya.